Obesity, chronic kidney disease progression and the role of the adipokine C1q/TNF related protein-3 - Diego Barbieri; Marian Goicoechea; Eduardo Verde; Ana García-Prieto; Úrsula Verdalles; Ana Pérez de José; Andrés Delgado; Maria Dolores Sánchez-Niño; Alberto Ortiz (Nefrología, 2023)
Introduction and aims: Obesity is a risk factor for incident chronic kidney disease (CKD). C1q/TNF related protein 3 (CTRP3) is an adipokine with multiple effects and may modulate the association between obesity and vascular diseases. The aim of the study is to explore potential links between obesity, CTRP3 levels and CKD progression. Methods: Patients with stage 3 and 4 CKD without previous cardiovascular events were enrolled and divided into groups according to body mass index (BMI) and sex. Demographic, clinical, analytical data and CTRP3 levels were collected at baseline. During follow-up, renal events (defined as dialysis initiation, serum creatinine doubling or a 50% decrease in estimated glomerular filtration rate were registered). Results: 81 patients were enrolled. 27 were obese and 54 non-obese. Baseline CTRP3 was similar between both groups (90.1 ± 23.8 vs 84.5 ± 6.2; p = 0.28). Of the sum, 54 were men and 27 women, with higher CTRP3 in women (81.4 ± 24.7 vs 106 ± 24.7; p < 0.01). During a mean follow-up of 68 months, 15 patients had a renal event. Patients in the higher CTRP3 tertile had less events but without statistical significance (p = 0.07). Obese patients in the higher CTRP3 tertile significantly had less renal events (p = 0.049). By multiple regression analysis CTRP3 levels could not predict renal events (HR 0.98; CI95% 0.96–1.06). Conclusions: CTRP3 levels are higher in woman than men in patients with CKD, with similar levels between obese and non obese. Higher CTRP3 levels at baseline were associated with better renal outcomes in obese patients. Resumen: Introducción: La obesidad es un factor de riesgo de la enfermedad renal crónica (ERC) incidente. La proteína 3 relacionada con C1q/TNF (CTRP3) es una adipoquina que puede modular la asociación entre obesidad y enfermedades vasculares. El objetivo del estudio es explorar los posibles vínculos entre obesidad, CTRP3 y progresión de ERC. Métodos: Pacientes con ERC estadio 3 y 4 sin eventos cardiovasculares previos fueron reclutados y divididos según el índice de masa corporal y sexo. Los datos demográficos, clínicos, analíticos y los niveles de CTRP3 se recopilaron basalmente. Durante el seguimiento se registraron eventos renales (inicio de diálisis, duplicación de la creatinina o una disminución del 50% en la filtración glomerular estimada). Resultados: Se reclutaron 81 pacientes, 27 obesos y 54 no obesos. LA CTRP3 inicial fue similar en ambos grupos (90,1 ± 23,8 vs. 84,5 ± 6,2; p = 0,28). Del total, 54 eran varones y 27 mujeres, con mayor CTRP3 en mujeres (81,4 ± 24,7 vs. 106 ± 24,7; p < 0,01). Durante un seguimiento medio de 68 meses, 15 pacientes sufrieron un evento renal. Los pacientes en el tercil superior de CTRP3 tuvieron menos eventos, pero sin significación estadística (p = 0,07). Los pacientes obesos en el tercil superior de CTRP3 tuvieron significativamente menos eventos renales (p = 0,049). Por análisis de regresión múltiple, los niveles de CTRP3 no pudieron predecir eventos renales (HR: 0,98; IC 95%: 0,96-1,06). Conclusiones: Los niveles de CTRP3 son más altos en mujeres que en varones en pacientes con ERC, con niveles similares entre obesos y no obesos. Valores iniciales mayores de CTRP3 se asociaron con mejores resultados renales en pacientes obesos.